Peran Pemerintah Desa dalam Pelaksanaan Aplikasi Sipraja di Desa Sugihwaras Kecamatan Candi Kabupaten Sidoarjo - Alyssa Puteri Nabilah; Deby Febriyan Eprilianto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Public services continue to develop and become more modern. The central, regional, and village governments continue to follow technological developments to support public administration activities so that services provided to the public can be maximized. The implementation of e-government in Indonesia is the foundation for strengthening more transparent, efficient, and community-oriented governance. SIPRAJA was launched by the Sidoarjo Regency Government as an application-based public service to meet community needs that is expected to help manage administrative needs digitally to speed up and facilitate services. The purpose of this study was to determine the role of the Sugihwaras Village Government, Candi District, Sidoarjo Regency in implementing the SIPRAJA application. The type of research used is a qualitative descriptive research method. The theory used is the theory of the role of village government according to Gito Saputro and Rangga which consists of five indicators, namely as a problem solver, facilitator, system connector, motivator, and communicator. Data collection techniques through observation, interviews, and documentation. Interviews were conducted with the Sugihwaras Village Government and the community. The results of the study indicate that the role of the Sugihwaras Village Government has made very good efforts in implementing the SIPRAJA application.